N170 Changes Show Identifiable Chinese Characters Compete Primarily with Faces Rather than Houses - Fan, Cong; He, Weiqi; He, Huamin; Ren, Guofang; Luo, Yuejia; Li, Hong; Luo, Wenbo (Frontiers in Psychology, 2016)
Character processing is a crucial cognitive skill that is highly emphasized and industriously cultivated in contemporary society. In the present study, using a competition paradigm, we examined the electrophysiological correlates of different relationships between Chinese characters and faces and between Chinese characters and houses during early visual processing. We observed that identifiable Chinese characters compete primarily with faces rather than houses at an early visual processing stage, with a significantly reduced N170 for faces but not for houses when they were viewed concurrently with identifiable Chinese characters relative to when they were viewed concurrently with unidentifiable Chinese characters. Consistent with our previous study, there was a significant increase in N170 after characters have been learned, indicating a modulatory effect of Chinese character identification level on N170 amplitude. Furthermore, we found an enlarged N170 in response to faces compared to houses, indicating that the neural mechanisms for processing faces and houses are different at an early visual processing stage.